Reconstruction Indigenous Science into Scientific Science in Roof Tile Production as Chemistry Material Learning (International Journal of Active Learning, 2022)
This study aims to explore and reconstruct community knowledge into scientific knowledge about the process of making Sokka roof tiles carried out by the people of Kedawung Village, Pejagoan District, Kebumen Regency, Central Java Province. The research method used is a qualitative method with an ethnoscience phenomenological approach. The research instruments used were observation sheets and interviews. The stages of the research were observation, verification, reconstruction, formulation, and conceptualization and documentation. Descriptive data analysis was also carried out for the data on the transformation of indigenous people's science and local wisdom into scientific science. The analysis results show that the owners and craftsmen have good techniques and methods and innovative ideas to produce quality roof tiles. The results showed that the chemical concepts in making Sokka Kebumen roof tiles were the nomenclature of compounds, hydrocarbons, reaction rates, and colloids. The expected output of this research is as a contextual learning resource for science teachers in schools to grow the students' scientific literacy.